Future groundwater extraction scenarios for an aquifer in a semiarid environment: case study of Guadalupe Valley Aquifer, Baja California, Northwest Mexico - Campos-Gaytan, Jose Ruben; Kretzschmar, Thomas; Herrera-Oliva, Claudia Soledad (Environmental monitoring and assessment, 2014)
Semiarid northwestern Mexico presents a growing water demand produced by agricultural and domestic requirements during the last two decades. The community of Guadalupe Valley and the city of Ensenada rely on groundwater pumping from the local aquifer as its sole source of water supply. This dependency has resulted in an imbalance between groundwater pumpage and natural recharge. A two-dimensional groundwater flow model was applied to the Guadalupe Valley Aquifer, which was calibrated and validated for the period 1984–2005. The model analysis verified that groundwater levels in the region are subject to steep declines due to decades of intensive groundwater exploitation for agricultural and domestic purposes. The calibrated model was used to assess the effects of different water management scenarios for the period 2007–2025. If the base case (status quo) scenario continues, groundwater levels are in a continuous drawdown trend. Some wells would run dry by August 2017, and water demand may not be met without incurring in an overdraft. The optimistic scenario implies the achievement of the mean groundwater recharge and discharge. Groundwater level depletion could be stopped and restored. The sustainable scenario implies the reduction of current extraction (up to about 50 %), when groundwater level depletion could be stopped. A reduction in current extraction mitigates water stress in the aquifer but cannot solely reverse declining water tables across the region. The combination of reduced current extraction and an implemented alternative solution (such as groundwater artificial recharge), provides the most effective measure to stabilize and reverse declining groundwater levels while meeting water demands in the region.